[FIRECARE FOR SENIOR CITIZENS] (Tufts Archival Research Center, 2007)
Letter from Linda Bayless, director of the Sacramento Area Fire Fighters Burn Center Committee, thanking Karen Fernicola of the Tobacco Institute for the informational video she received "A Commitment for Life for Senior Citizens". Says that the video presentation has been exceedingly helpful.